2023
DOI: 10.3390/biomedicines11123112
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Infusion of DNA-Aptamer Raised against Advanced Glycation End Products Prevents Loss of Skeletal Muscle Mass and Strength in Accelerated-Aging Mice

Yusaku Mori,
Makoto Ohara,
Michishige Terasaki
et al.

Abstract: We have developed DNA aptamers that can inhibit the toxic effects of advanced glycation end products (AGE-Apts). We herein evaluated the effects of AGE-Apts on muscle mass and strength in senescence-accelerated mouse prone 8 (SAMP8) mice. Eight-month-old male SAMP8 mice received subcutaneous infusion of control DNA aptamers (CTR-Apts) or AGE-Apts. Mice in an age-matched senescence-accelerated mouse resistant strain 1 (SAMR1) group were treated with CTR-Apts as controls. The soleus muscles were collected after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…These observations suggest that increased AGE accumulation levels in the diabetic testes under insulin-resistant and hyperglycemic conditions could stimulate RAGE gene expression via oxidative stress generation in a positive feedback manner, which is a molecular target of the AGE-Apt treatment-induced improvement of seminiferous tubular dilation and sperm abnormalities. This study revealed that testicular AGE accumulation per se was not affected by the 6-week treatment with AGE-Apt, which was consistent with the present finding, indicating that AGE-Apt treatment suppressed oxidative stress and Rage upregulation in soleus muscles but did not affect skeletal muscular AGE accumulation in a mouse model of sarcopenia [41]. Accordingly, AGE-Apt functions as a blocker of the binding of AGEs to RAGE, which could subsequently reduce oxidative stress generation and inflammation in the diabetic testes, but it did not sufficiently inhibit oxidative-stress-induced AGE formation under insulin-resistant conditions in our model.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These observations suggest that increased AGE accumulation levels in the diabetic testes under insulin-resistant and hyperglycemic conditions could stimulate RAGE gene expression via oxidative stress generation in a positive feedback manner, which is a molecular target of the AGE-Apt treatment-induced improvement of seminiferous tubular dilation and sperm abnormalities. This study revealed that testicular AGE accumulation per se was not affected by the 6-week treatment with AGE-Apt, which was consistent with the present finding, indicating that AGE-Apt treatment suppressed oxidative stress and Rage upregulation in soleus muscles but did not affect skeletal muscular AGE accumulation in a mouse model of sarcopenia [41]. Accordingly, AGE-Apt functions as a blocker of the binding of AGEs to RAGE, which could subsequently reduce oxidative stress generation and inflammation in the diabetic testes, but it did not sufficiently inhibit oxidative-stress-induced AGE formation under insulin-resistant conditions in our model.…”
Section: Discussionsupporting
confidence: 92%
“…AGEs have been shown to induce oxidative stress generation and inflammatory responses, such as Mcp-1 and Tnf-α gene expressions, through their interaction with RAGE in various cell types [ 12 , 13 , 14 ]. Furthermore, AGEs are reported to upregulate RAGE expression via oxidative stress generation, thereby forming a positive feedback loop between AGEs and RAGE-induced oxidative stress [ 40 , 41 ]. The present study revealed increased gene expression levels of Rage following AGE accumulation in the testes of 4-week-old DM mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations